Host species and developmental stage, but not host social structure, affects bacterial community structure in socially polymorphic bees. Issue 2 (6th May 2014) - McFrederick, Quinn S.; Wcislo, William T.; Hout, Michael C.; Mueller, Ulrich G.
Abstract: Social transmission and host developmental stage are thought to profoundly affect the structure of bacterial communities associated with honey bees and bumble bees, but these ideas have not been explored in other bee species. The halictid bees Megalopta centralis and M. genalis exhibit intrapopulation social polymorphism, which we exploit to test whether bacterial communities differ by host social structure, developmental stage, or host species. We collected social and solitary Megalopta nests and sampled bees and nest contents from all stages of host development. To survey these bacterial communities, we used 16S rRNA gene 454 pyrosequencing. We found no effect of social structure, but found differences by host species and developmental stage. Wolbachia prevalence differed between the two host species. Bacterial communities associated with different developmental stages appeared to be driven by environmentally acquired bacteria. A Lactobacillus kunkeei clade bacterium that is consistently associated with other bee species was dominant in pollen provisions and larval samples, but less abundant in mature larvae and pupae. Foraging adults appeared to often reacquire L. kunkeei clade bacteria, likely while foraging at flowers. Environmental transmission appears to be more important than social transmission for Megalopta bees at the cusp between social and solitary behavior. Abstract : Bacteria are important for social bee health, but we find that host species and host developmental stage instead of host social structure affects bacterial community structure.